2010
DOI: 10.1007/s12041-010-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the pituitary growth hormone gene and its receptor associated with coronary artery disease in a predisposed cohort from India

Abstract: We investigated the promoter polymorphisms of the pituitary growth hormone gene (GH1) and exon 3 deletion polymorphism (GHRd3) in its receptor gene (GHR) in 299 angiographically proven patients with coronary artery disease (CAD) and 231 asymptomatic controls enrolled in the ongoing Indian Atherosclerosis Research Study. Real time PCR based analysis of the GHR variant showed significant association of the GHRd3 deletion allele with CAD (OR 0.48, 95% CI: 0.30-0.76, P = 0.0014) and a dominant model of inheritance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In this study, we identified that the BWM gene SNP rs2005172 appears to have an impact on the pathological progression of renal fibrosis. The specific mechanism involves impairing glomerular permeability, stimulating epithelial–mesenchymal transition of podocytes, and promoting the expression of the fibrosis-associated classic molecule - transforming growth factor β ( 34 , 35 ). Meanwhile, rs35874463 has also been confirmed to enhance inflammatory responses and increase the transcription levels of the fibrosis signaling pathway transforming growth factor β/smads, thereby exacerbating renal fibrosis ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified that the BWM gene SNP rs2005172 appears to have an impact on the pathological progression of renal fibrosis. The specific mechanism involves impairing glomerular permeability, stimulating epithelial–mesenchymal transition of podocytes, and promoting the expression of the fibrosis-associated classic molecule - transforming growth factor β ( 34 , 35 ). Meanwhile, rs35874463 has also been confirmed to enhance inflammatory responses and increase the transcription levels of the fibrosis signaling pathway transforming growth factor β/smads, thereby exacerbating renal fibrosis ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%